Mahi‐mahi (Coryphaena hippurus) life development: morphological, physiological, behavioral and molecular phenotypes. Issue 5 (5th April 2019) - Perrichon, Prescilla; Stieglitz, John D.; Xu, Elvis Genbo; Magnuson, Jason T.; Pasparakis, Christina; Mager, Edward M.; Wang, Yadong; Schlenk, Daniel; Benetti, Daniel D.; Roberts, Aaron P.; Grosell, Martin; Burggren, Warren W.
Abstract: Background: Mahi‐mahi ( Coryphaena hippurus ) is a commercially and ecologically important fish species that is widely distributed in tropical and subtropical waters. Biological attributes and reproductive capacities of mahi‐mahi make it a tractable model for experimental studies. In this study, life development of cultured mahi‐mahi from the zygote stage to adult has been described. Results: A comprehensive developmental table has been created reporting development as primarily detailed observations of morphology. Additionally, physiological, behavioral, and molecular landmarks have been described to significantly contribute in the understanding of mahi life development. Conclusion: Remarkably, despite the vast difference in adult size, many developmental landmarks of mahi map quite closely onto the development and growth of Zebrafish and other warm‐water, active Teleost fishes. Key Findings: Mahi‐mahi is a tractable model for experimental studies high‐performance pelagic predatory fish species. Biological attributes of mahi are reported in a comprehensive developmental table. Physiological, behavioral and molecular landmarks are described through the life development. Mahi has a rapid growth rate, but the developmental marks are similar to other teleost fishes.